Child nutritional status, welfare and health in Nigerian households - Edeh, Hyacinth O.; Mavrotas, George; Adesugba, Margaret Abiodun (International Food Policy Research Institute, 2018)
The study attempts to provide insights into the relationships among child nutritional status, welfare and health among households and how these have evolved in Nigeria using the 2003, 2008, and 2013 children recode data of the Demographic and Health Survey (DHS) for Nigeria. We proxy welfare by using the wealth index of the DHS that captures wealth over time. Descriptive statistics and multilevel mixed-effects probit analysis were used to ascertain the linkages among child nutritional status, wealth, and health. The descriptive results show that malnutrition among under-5 children varies across the different wealth index levels with 50% and 35% of the children under-5 in the bottom two quintiles of the wealth index stunted and underweight, respectively. Results of the mixed-effects probit model also show that a child from a household with lower welfare is more likely to be malnourished. Our results also show that between 2003 and 2013, there has been no significant change in the wealth index levels between the richest and the poorest households. The study concludes that a household welfare level that is above average motivates increased nutritional levels among women and children in households and reduces the incidence of disease. Policies and practices that would increase the welfare of households would also have impacts on the nutritional status of households, especially those in the northern parts of Nigeria.